DEVELOPING STUDENTS' CRITICAL AND CREATIVE THINKING TO ENHANCE FUNCTIONAL LITERACY IN CHEMISTRY LESSONS - Arzimurodova Khonbuvi Jamol kizi (Bright Mind Publishing, 2025)
This article explores effective pedagogical strategies for developing students' critical and creative thinking skills in chemistry lessons as a means to enhance their functional literacy. In today's rapidly evolving scientific and technological landscape, the ability to analyze, interpret, and apply chemical knowledge to real-world problems is essential for students’ academic and personal growth. The paper examines the integration of problem-based learning, inquiry-based instruction, and project-based tasks to stimulate higher-order thinking. Through the implementation of contextual and interdisciplinary approaches, the research highlights how functional literacy in chemistry can be improved by fostering cognitive flexibility, reflective reasoning, and innovation among learners.
Keywords: Functional literacy, critical thinking, creative thinking, chemistry education, problem-based learning, cognitive development, interdisciplinary approach, higher-order thinking, student engagement, educational innovation.